(untitled) (PERcursos Linguísticos, 2020)
Anchored in Bakhtin’s perspective and in other researches related to it, this paper studies the winning chronicles of the 5th Portuguese Language Olympiad Writing the Future (hereinafter, OLPEF), held in 2016. Our aim is to analyze the interrelationships established between the prescriptions of this competition for the writing of chronicles and the constitution of the subject-authors, by identifying the positions assumed by the students’ voices. We verified how the students, in their compositions, dealt with the Program’s guidelines and registered their points of view, with a closer look at the ways in which they represented their local daily life, the place where they live. The results show that the students appropriated the rules of the olympiad, but they have also marked their positions through thematic representations, discursive strategies and unforeseen linguistic and stylistic resources. In other words, they subverted part of the prescribed generic constraints, properly establishing what they mean, their values in relation to OLPEF.